Differences in Biochar Sources for Controlled Nitrogen Loss in a Hybrid Maize Agroforestry System with Melaleuca cajuputi - Dody Kastono; Priyono Suryanto; Rohlan Rogomulyo; Suci Handayani; Supriyanta Supriyanta; Muhammad Habib Widyawan; Taufan Alam (Journal of Engineering and Technological Sciences, 2022)
Biochar is used to improve soil fertility and control nitrogen loss in soil. This study aimed to evaluate the difference between biochar sources, namely Melaleuca cajuputi waste and rice husk, for controlled nitrogen loss in hybrid maize planted between Melaleuca cajuputi stands. A split-plot design with three replications was used. The main plot was composed of biochar sources (BS), i.e., without biochar application (WB), Melaleuca cajuputi biochar (MCB), and rice husk biochar (RHB). The subplot was the urea fertilizer dosage, i.e., 0, 150, 300, and 450 kg/ha. The observation parameters were nitrate reductase activity (NRA), total chlorophyll (TC), leaf photosynthesis rate (LPR), nitrogen loss (NL), nitrogen use efficiency (NUE), and seed yield per hectare (SY). The data were analyzed with ANCOVA and LS-means. The results showed that there was no significant difference between mixing MCB or RHB in UF for all hybrid maize parameters, whereas significant differences were observed with WB. The NL values ​​of MCB and RHB were 13.85 and 13.08 kg/ha N, i.e., NL was significantly reduced by 70.90% and 72.51%, and the percentage of SY increased by 28.60% and 37.94% compared to WB, respectively.